Pengembangan Permainan Ular Tangga dalam Mengembangkan Nilai Agama Anak Usia Dini - Fadila, Sisca Nurul (Journal of Early Childhood Education (JECE), 2024)
Religious education is basically fostering or preserving the religious nature of children brought from birth. Religious education is important to be given from an early age as a foundation so that the ability to choose and decide develops properly, but the development of religious aspects in early childhood education institutions is still not in accordance with the characteristics of children's learning and thinking abilities. Children understand the world using symbolic functions (symbols) and exploration of the surrounding environment. So that concrete objects or media are needed. Based on these conditions, this study aims to produce game products that can stimulate and develop religious aspects of early childhood in 5 aspects of PAI. This study uses a research and development model using the Borg & Gall model. The research was conducted by involving teachers and children in early childhood education institutions both Islamic and general based. Based on the results of data analysis, it shows that the snakes and ladders game produced has a very valid quality and is very feasible to be used by teachers in developing religious aspects in children aged 5-6 years.